NGOs and Post-Conflict Recovery The Leitana Nehan Women?s Development Agency, Bougainville - Hakena, Helen; Ninnes Bert Jenkins, Peter; Jenkins, Bert (ANU Press, 2006)
Non governmental organizations; Women; History; Papua new guinea